Analysis of Teachers' Teaching Patterns Based on Transcript Based Lesson Analyses (TBLA) on Temperature and Heat Materials - Susanti, Nova; Aprian, Ulfa Zuhroh Twenty (Journal of Learning Improvement and Lesson Study, 2022)
This study is a study that aims to analyze the teacher's learning patterns in the classroom through transcript-based lesson analysis (TBLA)-based lesson study. There are 3 main stages in this research, which consist of planning (plan), implementation (do), and reflection (see) which are carried out in 2 cycles. The study was conducted in November 2020. The data collection in this study used learning video recordings, observation sheets, and documentation of other artifacts. In cycle 1, the results of the analysis of the pattern of teaching dialogue were dominated by exposition so that fewer discussions were formed. Cycle 2 lesson study is intended to improve learning in cycle 1 so that cycle 2 is carried out based on the results of the reflection of cycle 1. The results of the analysis of dialogue patterns in cycle 2 there is a pattern of teaching dialogue formed in learning consisting of pronunciation, exposition, and discussion so that the number of discussion engagements between teachers and students are more dominant and this result shows that a good teaching dialogue pattern will have a good impact on students' scientific attitudes. From the results of this study, it is suggested that teachers can apply lesson study based on transcript-based lesson analyses. The application of this technical analysis will enable teachers to improve their ability to make learning that will be implemented more effective